The role of context and professional agency in the spread of healthcare innovation: an exploratory study of healthcare professionals' views of diabetes self-management and the X-PERT Programme - Go Jefferies, Josephine K. W. (2012)
This study explores the views of a network of healthcare professionals who, in addition to their main clinical roles and related professional training duties, are also trained patient educators (Educators) delivering a structured education (SE) programme to adults with diabetes. The author engages with literature on self-management and institutional change in healthcare and closely considers factors affecting implementation of self-management and structured education. The research aims to show the mental framing that Educators use when considering self-management, and the implications for the spread of self-management diffusion at the micro-organisational level. It does this by analysing Educators’ beliefs and attitudes to diabetes self-management and SE, and then situates their responses using theoretical frameworks to identify and explain institutional change processes taking place. Echoing Coulter’s (2012) findings from her study into leadership and patient engagement, my study shows that healthcare professionals hold positive views about being an Educator chiefly as it allows them to acquire new knowledge and skills, which allows them to improve professional effectiveness and patient outcomes. This can be interpreted as new cultural-cognitive and normative elements creating a new institutional logic at the micro-organisational level. Being an Educator also allows them to mitigate effects of poor practice elsewhere in the diabetes care network resulting in better patient outcomes; they do this through exploiting micro-institutional affordances in a highly structured institution like the NHS. This enactment can be interpreted as forming new regulative elements. The study makes a novel contribution to the literature on self-management by addressing the views of healthcare professionals and healthcare innovation by showing how their engagement means self-management is becoming institutionalised.